ANALISIS PENGARUH KUALITAS INFORMASI DAN KUALITAS SISTEM TERHADAP KEPUASAN PENGGUNA SISTEM E-FILING - Hidayati, Nur; Harimurti, Fadjar; SPA, Dewi (Riset Akuntansi dan Keuangan Indonesia, 2017)
This study aimed to analyze the effect quality of information system and quality of information onÂ  user satisfaction of e-filing system. The object of the research is conducted at the Tax Services Office (KPP) Pratama Karanganyar, using sample of 100 respondent with purposive sampling technique. Collecting data using questionnaire techniques, data analysis techniques using multiple linear regression analysis. The conclusion of each hypothesis test results show that (1) quality of information system have significant effect on user satisfaction of e-filing system. (2) quality of information have significant effect on user satisfaction of e-filing system. Implication of this study, increased the quality of information system and quality of information can influencing increased on user satisfaction of e-filing system.Â Keywords: quality of information system, quality of information, user satisfaction of e-filing systemÂ